Design and control of piezoelectric-driven handheld manipulator for tremor compensation in microsurgery - Tan, U Xuan (2010)
The problem of correcting imprecision due to physiological hand tremor while performing micromanipulation tasks such as microsurgery has received considerable attention. This results in the development of a hand-held instrument, Micron, that senses its own motion using an inertial measurement unit; distinguishes intended and undesired motion, and actively attenuates the undesired motion by an opposite but equal deflection of the tip through a piezoelectric-driven manipulator. This dissertation emphasizes an improved version of the aforementioned instrument with regards to the design and control of the piezoelectric-driven mechanism.